2021
DOI: 10.1186/s13287-021-02525-0
|View full text |Cite
|
Sign up to set email alerts
|

Transition from static culture to stirred tank bioreactor for the allogeneic production of therapeutic discogenic cell spheres

Abstract: Background Culturing cells as cell spheres results in a tissue-like environment that drives unique cell phenotypes, making it useful for generating cell populations intended for therapeutic use. Unfortunately, common methods that utilize static suspension culture have limited scalability, making commercialization of such cell therapies challenging. Our team is developing an allogeneic cell therapy for the treatment of lumbar disc degeneration comprised of discogenic cells, which are progenitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This includes the important proteoglycan, aggrecan, which has been measured in a protein assay. 15 Discogenic cells are allogeneic, as they are derived from adult human organ donors. However, we have observed that discogenic cells appear to be immune-privileged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes the important proteoglycan, aggrecan, which has been measured in a protein assay. 15 Discogenic cells are allogeneic, as they are derived from adult human organ donors. However, we have observed that discogenic cells appear to be immune-privileged.…”
Section: Discussionmentioning
confidence: 99%
“…Second, discogenic cells lack expression of co-stimulatory molecules CD40, CD80, and CD86, which are required for effector T cell induction. 13,15 The cells do not form tumors in vitro or in vivo. Studies testing human IDCT in animal models of disc degeneration have shown IDCT to be safe and bioactive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to optimize the hydrodynamic profile (agitation rate) by understanding the effect of maximum shear stress on the cells. 24,25 Although these bioreactors are very helpful in the mass production of therapeutic cells and their products, the major limitation is the inability to support nutrient supply to the core regions of the tissue engineered scaffolds. For example, mass transfer of nutrients to the periphery of the bone scaffold was found to be higher when compared to the core regions.…”
Section: Stirred Tank Bioreactorsmentioning
confidence: 99%
“…A work by Rodriguez-Granrose et al demonstrated the transition from static culture to a stirred-tank bioreactor. The study assessed the production of beads in the Erlenmeyer system and of discogenic cells for the development of cell therapy for the treatment of lumbar disc degeneration [ 169 ]. On the other hand, Manstein et al combined STBR with the power of in silico process modeling for the best results in a human pluripotent stem cell (hPSC) culture [ 170 ].…”
Section: The 3d Cell Culturementioning
confidence: 99%